Prevention of interferon‐alpha‐associated depression with antidepressant medications in patients with hepatitis C virus: a systematic review and meta‐analysis. Issue 2 (22nd December 2013) - Ehret, M.; Sobieraj, D. M.
Summary Objective To conduct a systematic review and meta‐analysis evaluating the efficacy and safety of antidepressant medications for the prevention of interferon‐alpha (INF‐α)‐associated depression in patients with chronic hepatitis C virus (HCV). Data sources Medline, Cochrane Central and PsycInfo from inception to September 2012, without limitations using terms describing hepatitis C and the individual drug names. Study selection We reviewed 132 citations for inclusion using the following criteria: randomised controlled trials in patients with chronic HCV initiating INF‐α comparing prophylactic use of an antidepressant vs. placebo and reporting at least one outcome of interest [depression, completion of antiviral therapy, sustained virologic response (SVR), and serious adverse events and bleeding]. Data extraction Trial characteristics, assessment of risk of bias and data needed for analyses were extracted by two independent investigators using a standard extraction form. Disagreements were reviewed by a third investigator. Results A DerSimonian and Laird random‐effects model was used for analysis. Heterogeneity and publication bias were evaluated where applicable. Of the seven included trials, the risk of bias was low in four and unclear in the remaining three. All trials evaluated selective serotonin reuptake inhibitors (SSRIs). Prophylactic use of a SSRI significantly reduced the risk of depression by 41% compared with placebo [RR, relative risk 0.59 (0.37–0.93)]. The impact of SSRIs on completion of antiviral therapy, SVR and serious adverse events was not found to be significant. Conclusions SSRIs prevent depression in patients with HCV treated with INF‐α therapy. The impact of SSRIs on completion of antiviral therapy or on the development of adverse events is less clear.